Digital Storytelling and Brand Trust Drive Generation Z in Skincare Purchase Decisions - Maulana Aditya Alfian Noor; Rizky Aditya Wirayudha; Siska Ernawati Fatimah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Changes in the behavior of Generation Z consumers, who are women and even men, can consciously be aware of self-care. This aligns with technological developments that make it easier for them to find information through social media, compare products, and see skincare user testimonials, which can encourage them to make effective purchasing decisions. This study examines how brand trust and digital storytelling affect consumers' buying decisions. It employs a quantitative approach focusing on Generation Z individuals aged 14-27 years in Cirebon City, which has a population of 117,229 people. The sample calculation uses the Slovin formula, with the calculation results obtained from 400 respondents. The data analysis method employed is Structural Equation Modeling using Partial Least Squares (SEM-PLS). This research shows that brand trust and digital storytelling greatly impact Cirebon City residents' decisions to buy skincare products. Trust dominates the influence on purchasing decisions because consumers are more careful in choosing skincare products through the information obtained, which is supported by other user reviews. Skincare industry players are expected to use the study's findings to inform their social media marketing tactics, which will drive more consumer purchases and boost sales growth while preserving business stability. The implications of this research are expected to be utilized by skincare business operators in determining their marketing strategies through social media to encourage increased consumer purchasing decisions, thereby boosting sales growth to maintain business stability, enabling them to compete and contribute to economic growth.